1981
DOI: 10.2355/isijinternational1966.21.135
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Phosphorus from LD Converter Slag by Floating Separation of Dicalcium Silicate during Solidification

Abstract: SynopsisMineralogical study of LD converter slag was carried out by means of microscopic and EPMA examinations and phosphorus was found to exist only in dicalcium silicate as solid solution. This led to the study of separation of dicalcium silicate from LD converter slag in order to remove phosphorus.When liquid slag was solidified slowly, most dicalcium silicate particles accumulated in the top part of the crucible and fewer in the bottom. The phenomena can be interpreted as follows; on solidification, dicalc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 0 publications
4
28
1
Order By: Relevance
“…18) Ono 3) suggested that when liquid BOF slag solidified slowly, most dicalcium silicate was crystallized primarily and accumulated in the top part of slags. CaO, SiO 2 and P 2 O 5 were enriched in the top, while FeO, Fe 2 O 3 and MnO in the bottom.…”
Section: Difference Between Dephosphorization Slag Andmentioning
confidence: 99%
See 1 more Smart Citation
“…18) Ono 3) suggested that when liquid BOF slag solidified slowly, most dicalcium silicate was crystallized primarily and accumulated in the top part of slags. CaO, SiO 2 and P 2 O 5 were enriched in the top, while FeO, Fe 2 O 3 and MnO in the bottom.…”
Section: Difference Between Dephosphorization Slag Andmentioning
confidence: 99%
“…Ono et al 3) developed a method for removal of phosphorus by floating separation of dicalcium silicate during slow solidification. Li et al 4) proposed a slag regeneration process to reduce the BOF slag in an iron bath furnace, and then the high phosphorus hot metal obtained from the reduction process was dephosphorized to get high P2O5 content slag for the use of fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, leaching results indicated that the C 2 S in the testwork sinter was also enriched in Cr and K with respect to the bulk composition. Many researchers have investigated the substitutions of various components into C 2 S [39][40][41] and in the fields of iron and steelmaking there has been a particular focus on P [36][37][38] (because it is an undesirable contaminant). Some iron-making literature contains data for the partitioning of foreign components into C 2 S at low temperatures (down to ϳ1 300°C), 39) but the great majority of research to date has focused on high temperature molten metal/slag mixes and not C 2 S in ore agglomerates.…”
Section: Chemistry and Crystal Structure Of C 2 S In Sintermentioning
confidence: 99%
“…30,39) 3) C 2 S is known to incorporate a wide variety of impurities in several different systems, including those relevant to the cement industry [39][40][41] and steelmaking slags, where they preferentially concentrate undesirable components. [36][37][38] 4) The incorporation of impurities in the crystal lattice can stabilise different polymorphs of C 2 S and thereby inhibit phase transformations. 39,41) 5) At least one polymorph of C 2 S (b) is known to gelatinise in dilute HCl 42) and the hydration of C 2 S is well understood in the cement industry.…”
Section: Dicalcium Silicatesmentioning
confidence: 99%
See 1 more Smart Citation